Kandungan Logam Berat Kadmium (Cd) dan Tembaga (Cu) pada Sedimen dan Siput Strombus Canarium Pantai Pulau Bintan - Nasution, Syafruddin (Jurnal Natur Indonesia, 2011)
This research was conducted at North Bintan island waters. The sample of sediment and snail S. canarium hasbeen taken from four locations those were Busung, Lobam, Sebung, and Tanjung Bakau coastal waters. Analysisof metal concentrations both in sediment and snail conducted by using Atomic Absorption Spectrophotometer(AAS)Solar 969 AA. The result showed the highest concentration of Cadmium (Cd) and Cuprum (Cu) in sediment whichwere 0.51 ppm (Cd) and 13.22 ppm (Cu). While the highest concentration of these metals in snail S. Canarium wichwere 0.56 ppm (Cd) and 8.42 (Cu), indicating that the concentration in both sediment and snail still below thenormal threshold. It could be concluded that the Bintan Coast has not been polluted but lightly contaminated.